Efektivitas mandatory training tentang keperawatan berbasis syariah terhadap kemapmpuan penegakan diagnosis keperawatan spiritual - Mulyati, Mimin; Abdurrouf, Muh; Sari, Dyah Wiji Puspita; Ardian, Iwan (Holistik Jurnal Kesehatan, 2025)
Background: Sharia-based nursing care emphasizes fulfilling patients’ biological, psychological, social, and spiritual needs by integrating the principles of maqashid sharia. Spiritual nursing diagnoses are an essential component as they influence patients’ recovery and quality of life; however, nurses’ ability to establish these diagnoses remains low. Purpose: To evaluate the effectiveness of mandatory training on sharia-based nursing on the ability to enforce spiritual nursing diagnoses. Method: A pre-experimental one-group pretest–posttest design was applied to 76 nurses at Sari Asih Ciputat Hospital who met the PK II/Sharia Nurse II criteria. Data were collected using pretest–posttest questionnaires and practice observation sheets, then analyzed using a paired t-test with a significance level of α = 0.05. Results: The mean pretest score of 54.27 (SD = 22.17) increased to 67.63 (SD = 16.98) after the intervention, showing a statistically significant difference (t = -12.292; df = 71; p < 0.001; 95% CI: -15.52 to -11.19). The proportion of nurses who could optimally establish spiritual nursing diagnoses increased from 54.2% to 83.4% after mentoring. Observation results also indicated consistent improvement in practical skills. Conclusion: These findings demonstrate that sharia-based mandatory training with mentoring is effective in improving nurses’ competence in spiritual assessment and diagnosis. Suggestion: The implementation of continuous practice-based training to strengthen nurses' spiritual competencies and improve the quality of nursing services based on Sharia.   Keywords: Mandatory Training; Mentoring; Nursing Diagnosis; Sharia-Based Nursing; Spiritual.   Pendahuluan: Pelayanan keperawatan berbasis syariah menekankan pemenuhan kebutuhan biologis, psikologis, sosial, dan spiritual pasien dengan mengintegrasikan prinsip maqashid syariah. Diagnosis keperawatan spiritual menjadi komponen penting karena memengaruhi pemulihan dan kualitas hidup pasien, namun kemampuan perawat dalam menegakkannya masih rendah. Tujuan: Untuk mengevaluasi efektivitas mandatory training tentang keperawatan berbasis syariah terhadap kemapmpuan penegakan diagnosis keperawatan spiritual. Metode: Desain penelitian menggunakan pre-eksperimental one group pretest-posttest pada 76 perawat dengan kriteria PK II/Perawat Syariah II. Data dikumpulkan melalui kuesioner pretest–posttest dan lembar observasi praktik, dianalisis menggunakan paired t-test dengan α = 0,05. Hasil menunjukkan Hasil: Rata-rata skor pretest 54.27 (SD = 22.17) meningkat menjadi 67.63 (SD = 16.98). Sementara itu, ketika posttest dengan perbedaan signifikan (t = -12.292; df = 71; p < 0.001; IK 95% -15.52 -11.19). Proporsi perawat yang mampu menegakkan diagnosis spiritual secara optimal meningkat dari 54.2% menjadi 83.4% setelah mentoring. Hasil observasi juga memperlihatkan peningkatan kemampuan praktik yang konsisten. Simpulan: Mandatory training berbasis mentoring efektif meningkatkan kompetensi perawat dalam pengkajian dan diagnosis spiritual. Saran: Penerapan pelatihan berkelanjutan berbasis praktik untuk memperkuat kompetensi spiritual perawat dan meningkatkan mutu pelayanan keperawatan berbasis syariah.   Kata Kunci: Diagnosis Keperawatan; Keperawatan Berbasis Syariah; Mandatory Training; Spiritual.